Pengaruh Kompetensi Sumber Daya Manusia, Pemanfaatan Sistem Informasi Akuntansi Keuangan Daerah, Sistem Pengendalian Intern Dan Peran Internal Audit Terhadap Kualitas Laporan Keuangan Pemerintah Daerah (Studi Empiris Pada SKPD Kabupaten Tegal) - Pramudityo, Bagus; , Dra. Rina Trisnawati, Ak, M.Si, Ph.D (2017)
This research aims to provide empirical evidence of influence: influence of human resource competencies, exploiting the area of financial accounting information system, internal control system, and the role of internal audit of the quality of financial reporting. Methods of sample collection was done by purposive sampling. This research was conducted using primary data. The population in this study is the manager of the work unit or ranking officials in the SKPD Tegal regency. The analytical method used is multiple regression analysis. The results of this study prove that the variable competence of human resources, utilization of local financial accounting information system, internal control system, and the role of internal audit affect the quality of financial reporting.